Seeds for Needs: participatory variety selection - Gevel, Jeske M.J, van de; Bioversity International; Gellaw, A.; Fadda, Carlo (Bioversity International, 2013)
A series of policy briefs bringing together the major results and policy recommendations of the Seeds for Needs project which started in 2009. The project was carried out in collaboration with the Institute of Biodiversity Conservation (IBC) in Ethiopia. This project provides a unique framework for combining an improved understanding of climate change scenarios in Ethiopia and available crop diversity information from a range of sources (including genebanks) with farmers’ own experience, indigenous knowledge and traditional adaptation strategies.